Effect of tryptone concentration on Cyclodextrin Glucanotranferase (CGTase) excretion and cell lysis of immobilized recombinant escherichia coli - Rohaida, Che Man; R., M. Illias; Siti Hajar, Shaarani; Z. I., M. Arshad; Siti Kholijah, Abdul Mudalip; Siti Zubaidah, Sulaiman; S. F. Z., Mohamad Fuzi; Abdul Adam, Abdullah (IOP Publishing, 2020)
The recombinant enzyme excretion into the culture medium provides significant advantages over cytoplasmic expression. Nevertheless, the problems encountered during the excretion of recombinant enzyme are the plasmid instability and occurrence of cell lysis. Various attempts have been made to improve the recombinant enzyme excretion and plasmid stability with the low occurrence of cell lysis. The approaches include the modification of the nitrogen sources in the medium such as tryptone, the use of cell immobilization system and lowering the induction temperature. In the present study, the effects of different tryptone concentrations (1, 5, 10, 20 and 30 g/L) as nitrogen source in super optimal broth (SOB) medium on CGTase excretion and plasmid stability as well as cell lysis of the immobilized cell were studied. The recombinant E. coli was immobilized on polyvinylidene fluoride polymer (PVDF) hollow fiber membrane. The immobilized cells were expressed using 0.011 mM IPTG at 25°C, 200 rpm of agitation rate and pH 8.8 for 24 h of post induction time. The use of low tryptone concentration (5 g/l) produced high CGTase excretion (758.64 U/ml) and increased the plasmid stability (86% increment) with reduction of cell lysis (90% reduction) in comparison with the initial tryptone concentration (20 g/l). Hence, low concentration of tryptone could reduce the cost for CGTase production due to low amount of tryptone used in the fermentation process.